2019
DOI: 10.1186/s41235-019-0183-2
|View full text |Cite
|
Sign up to set email alerts
|

Best-worst scaling improves measurement of first impressions

Abstract: A common goal in psychological research is the measurement of subjective impressions, such as first impressions of faces. These impressions are commonly measured using Likert ratings. Although these ratings are simple to administer, they are associated with response issues that can limit reliability. Here we examine best-worst scaling (BWS), a forced-choice method, as a potential alternative to Likert ratings for measuring participants’ facial first impressions. We find that at the group level, BWS scores corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…However, the same task could also be designed using other software packages, e.g., the supportBWS package for R (Aizaki et al, 2014), and presented in any online or paper medium. See Additional Files associated with Burton et al, 2019 for helpful materials including "A beginners guide to the process of designing, running and scoring a Best-Worst Scaling Task', annotated R scripts and supporting files.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the same task could also be designed using other software packages, e.g., the supportBWS package for R (Aizaki et al, 2014), and presented in any online or paper medium. See Additional Files associated with Burton et al, 2019 for helpful materials including "A beginners guide to the process of designing, running and scoring a Best-Worst Scaling Task', annotated R scripts and supporting files.…”
Section: Resultsmentioning
confidence: 99%
“…We also tested a group of adult participants on the same tasks. Based on the findings of Burton et al (2019) and Kiritchenko and Mohammad (2017), we also expected to find the same pattern of improved individual and group-level reliability for this adult group.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…In relation to biomedical image assessments, where evaluation considers the visual quality of the stimuli, Phelps et al [27] found that pairwise comparisons and ranked Likert scores made for more accurate assessments in comparison to the use of non-ranked Likert scores. Burton et al [2] compared rating scales with best-worst scaling, another variant of the rank-based approach. In this study, participants were asked to select the most attractive and least attractive faces in a series of images.…”
Section: Related Workmentioning
confidence: 99%